2009
DOI: 10.1172/jci39832
|View full text |Cite|
|
Sign up to set email alerts
|

A novel microRNA targeting HDAC5 regulates osteoblast differentiation in mice and contributes to primary osteoporosis in humans

et al.

Abstract: MicroRNAs (miRNAs) interfere with translation of specific target mRNAs and are thought to thereby regulate many cellular processes. Recent studies have suggested that miRNAs might play a role in osteoblast differentiation and bone formation. Here, we identify a new miRNA (miR-2861) in primary mouse osteoblasts that promotes osteoblast differentiation by repressing histone deacetylase 5 (HDAC5) expression at the posttranscriptional level. miR-2861 was found to be transcribed in ST2 stromal cells during bone mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
347
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(361 citation statements)
references
References 43 publications
7
347
3
4
Order By: Relevance
“…Interestingly, other clusters have also been studied, such as the auto-regulatory feedback loops controlling Runx2 expression. miR-3960/-2861 is transactivated by Runx2 in vitro, thereby maintaining its own levels of expression by blocking the expression of Hoxa and Hdac5, negative regulators of osteoblast differentiation (Kanzler et al 1998, Dobreva et al 2006, Li et al 2009a, Hu et al 2011. Furthermore, an in vivo approach has demonstrated that Satb2 is also targeted by miR-34s, affecting osteoblast proliferation mainly by means of miR-34b and miR-34c.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, other clusters have also been studied, such as the auto-regulatory feedback loops controlling Runx2 expression. miR-3960/-2861 is transactivated by Runx2 in vitro, thereby maintaining its own levels of expression by blocking the expression of Hoxa and Hdac5, negative regulators of osteoblast differentiation (Kanzler et al 1998, Dobreva et al 2006, Li et al 2009a, Hu et al 2011. Furthermore, an in vivo approach has demonstrated that Satb2 is also targeted by miR-34s, affecting osteoblast proliferation mainly by means of miR-34b and miR-34c.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
“…The 3 0 -UTR of the ACVR1/ALK2 gene has recently been studied in vitro to elucidate miRNAs that when expressed induce BMP signaling alterations in fibrodysplasia ossificans progressiva (Mura et al 2012). Several additional BMP-modulated miRNAs have been identified (Li et al 2008, 2009a, Lin et al 2009, Bae et al 2012, Gamez et al 2013, generally as a result of high-throughput expression analysis but without precise information on their transcriptional control and function.…”
Section: The Interplay Between Mirnas and Bmp Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Экспрессия кластера подавляется RUNX2 в остеобла-стах. мкРНК2861 и мкРНК-3960, наоборот, опосредованно стимулируют экспрессию RUNX2, подавляя его ингибито-ры HDAC5 и HOXA2 и, соответственно, тем самым способ-ствуя дифференцировке остеобластов [45,46]. В определенной степени, остерикс (OSX) -транс-крипционный фактор, необходимый для формирования костной ткани, находится под контролем мкРНК, образуя уникальную ауторегуляторную петлю обратной связи с мкРНК93.…”
Section: роль мкрнк в костном ремоделированииunclassified
“…При изучении клинического случая редкой формы се-мейного остеопороза у 2 пациентов подросткового возрас-та была выявлена мутация мкРНК2861 [45]. Увеличение интенсивности экспрессии мкРНК2861 блокирует эпиге-нетический регулятор HDAC5, который посредством де-ацетилирования гистонов ингибирует остеобластогенез.…”
Section: актуальные вопросы эндокринологииunclassified